Salt stress induced accumulation of biomolecules in groundnut genotypes - Jharna, D. E.; Samanta, S. C. (JOURNAL OF ADVANCES IN AGRICULTURE, 2021)
Salinity is one of the environmental limiting factors in agricultural production. The aim of this study was to find out one of more salt tolerant groundnut genotypes through monitoring the growth and changes in biomolecules under salt stress condition. Purposively four groundnut genotypes, including a Traditional variety, Zhingabadam, Binachinabadam-1 and Dacca-1 were grown under three salinity levels viz. 0, 3 and 5 dSm-1. The experiment was laid out in two factorial completely randomized design with three replications. This experiment was done in soil based pot culture up to 40 days. Increasing salt concentration drastically reduced all the growth parameters, and increase proline and sugar content of leaf. Among the varieties Traditional variety, Zhingabadam and Dacca-1 had statistically similar shoot and root dry weight. The leaves of the Traditional variety contain the highest amount of proline of 14.52 and 36.24 mg/100g fresh leaves in 3 and 5 dS/m salinity, respectively which was 236 and 737 % higher than that of respective control. At EC of 3 and 5 dS/m, the variety Binachinabadam-1 was appeared to be susceptible, having an increase of 6 and 113% proline content over the respective control. Based on the shoot dry weight, root dry weight, proline content, total sugar, reducing sugar and relative water content, the Traditional variety was strongly recommended to be grown in the coastal salt affected soils. The Zhingabadam and Dacca-1 variety also could be recommended as they had comparable performance of the Traditional variety.